Effect of Perforated Aluminum on Calotropis Gigantea Fiber Material’s Ability to Absorption Sound - suhaeri, suhaeri; Husaini, Husaini; Dirhamsyah, Muhammad; Hasanuddin, Iskandar (Jurnal Polimesin, 2024)
Plants fibers such as Calotropis gigantea (CG) are very suitable as noise reduction material. Therefore, this research aims to determine the sound absorption coefficient of CG in the 20 mm test sample and the effect of the perforated aluminum layer on its ability. It was carried out using a test sample made with a thickness of 20 mm and 100 mm in diameter. The thickness of aluminum was 0.3 mm with hole diameters of 1 mm, 1.5 mm, and 2.5 mm. During the experiment, every sample was heated and pressed in a mold for 10 minutes at 200oC. The test equipment used is a Bruel Kjaer Type 4206 impedance tube with 100 mm in diameter. The sample was tested using the transfer function method ISO 10534-2:1998 at a frequency of 1/1 octave. The results indicated that the uncoated sample absorbed noise α = 0.01-0.07 (1-7)% higher than the sample coated with perforated aluminum. This showed that the Noise Reduction Coefficient (NRC) without aluminum coating can reduce noise by 29%, and the measured sample is categorized in class D.